Comparative study on calculation methods for local buckling critical stress of rectangular section FRP members. Issue 3 (March 2020) - Hu, Yifan; Yang, Zhipeng; Tao, Feiyu
Abstract: The prediction accuracy of the local buckling critical stress calculation formula of the existing FRP members is analyzed by the experimental data of the local buckling critical stress of the fiber reinforced polymer (FRP) members.Verification of the validity of the finite element model based on experimental data.The comparison results between the numerical simulation critical stress and the predicted value of the calculation formula after adjusting the size of the FRP member are obtained. The variation of the prediction accuracy of the existing calculation formula is studied.The research shows that the predictive value of the calculation method proposed by Strongwell in 1998 underestimated the database test data by 45.4%, and underestimated the finite element simulation result by 46.3%.It is the equation closest to the actual local buckling critical force of the PFRP member. As a general formula, predicting the local buckling critical stress of the PFRP member can improve the material utilization rate. After the research, it was found that the calculation formula proposed by Strongwell Company had a large error with the database test data, and there is still room for improvement.